ANALYSIS OF THE EFFECT OF INTERNAL COMMUNICATION EFFECTIVENESS AND PROCEDURAL JUSTICE ON THE STABILITY OF INDUSTRIAL RELATIONS THROUGH EMPLOYEE TRUST - Herry Prinanda; Osly Usman (CV Naskah Aceh, 2026)
Industrial relations stability is a cornerstone of sustainable business in the labor-intensive retail sector. Amid the dynamics of Indonesia's labor regulatory changes particularly following the Constitutional Court Decision No. 168/PUU-XXI/2023 on the Job Creation Law this study analyzes the effects of internal communication effectiveness and procedural justice on industrial relations stability, with employee trust as a mediating variable. An explanatory quantitative approach was employed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) via SmartPLS 4. A sample of 30 permanent retail employees in Jabodetabek was recruited through purposive sampling. Outer model evaluation confirmed convergent validity (AVE > 0.50), composite reliability (CR > 0.70), and discriminant validity (HTMT < 0.90) meeting scholarly standards. Bootstrapping with 5,000 subsamples revealed that internal communication (β=0.451; t=5.21; p<0.01) and procedural justice (β=0.382; t=4.37; p<0.01) significantly affect employee trust, which in turn strongly predicts industrial relations stability (β=0.523; t=6.18; p<0.001). Mediation testing confirmed partial mediation for the communication path (indirect β=0.236; p=0.002) and full mediation for the procedural justice path (indirect β=0.200; p=0.004). A complementary Artificial Neural Network (ANN) feedforward backpropagation analysis corroborated these findings, identifying two-way communication channel accessibility (X1.3) as the strongest predictor (normalized importance=0.29). Model R² values were 0.581 for Y and 0.612 for the mediator M.